The beginning of the biblical canon and Ben Sira - Brodersen, Alma (2023)
The Book of Ben Sira, written in Hebrew in the early second century BCE, is often regarded as containing the earliest references to the canon of the Hebrew Bible / Old Testament. In contrast, Alma Brodersen examines methodological and historical issues regarding the beginning of the biblical canon and Ben Sira, and demonstrates that the book itself - as distinct from the later Prologue to its Greek translation - does not actually refer to texts as canonical. In addition, a systematic analysis of key passages in Ben Sira 38-39 and 44-50 in Hebrew and Greek uncovers similarities with other ancient texts which are not canonical today but preserved in the Dead Sea Scrolls. Far from proving the existence of the biblical canon in his day, Ben Sira's book indicates instead the importance of oral teaching and the relevance of a wide range of traditions